2015
DOI: 10.5152/jtgga.2015.15156
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of effects of nifedipine and ritodrine on maternal and fetal blood flow patterns in preterm labor

Abstract: Results:In both the groups, early-and late-onset changes in the pulsatility index (PI) and other Doppler indices for UA, UtA, and MCA were similar. In addition, time elapsed till delivery, fetal mortality, and maternal morbidity in both the groups were not statistically significant (p>0.05). However, maternal side effects such as tachycardia was more frequent (p<0.05) in the ritodrine group. Besides, in the ritodrine group, anxiety was only minimally observed. Conclusion:Nifedipine and ritodrine used as tocoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…This is consistent with the study done by Baykal and Avcıoğlu where they did not find any significant difference in Doppler ultrasonography measurements of UtA or between Doppler indices for MCA at 2 h (early phase) and 48 h (late phase) after nifedipine treatment (p>0.05). 17 Our data showed that nifedipine tocolysis produced no differences in the umbilical arteries Doppler (RI and PI) or in the MCA to umbilical artery ratio, similar to the findings of Karahanoglu et al who found that RI, the PI and the S/D ratio of UA did not change after treatment with nifedipine. 18 Also, de Heus et al showed that over the 5-day study period.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with the study done by Baykal and Avcıoğlu where they did not find any significant difference in Doppler ultrasonography measurements of UtA or between Doppler indices for MCA at 2 h (early phase) and 48 h (late phase) after nifedipine treatment (p>0.05). 17 Our data showed that nifedipine tocolysis produced no differences in the umbilical arteries Doppler (RI and PI) or in the MCA to umbilical artery ratio, similar to the findings of Karahanoglu et al who found that RI, the PI and the S/D ratio of UA did not change after treatment with nifedipine. 18 Also, de Heus et al showed that over the 5-day study period.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have investigated the possible effects of nifedipine on fetomaternal blood flow . Two previous studies reported that nifedipine does not cause a significant change in uteroplacental and fetal Doppler parameters. These two studies evaluated patients in preterm labor who had received an oral nifedipine loading dose, followed by maintenance therapy.…”
Section: Discussionmentioning
confidence: 99%
“…These two studies evaluated patients in preterm labor who had received an oral nifedipine loading dose, followed by maintenance therapy. In one of these studies, the patients also received betamethasone. Two other studies showed significant effects of nifedipine on maternal and fetal vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these results it can be concluded that administration of nifedipine does not affect the welfare of the fetus, and does not cause any signs of placental insu ciency. 34 DV PI changes in blood ow before and after hours after nifedipine therapy Table 4.3 showed the mean DV PI before therapy was 0.50 ± 0.17, while the mean of DV PI after nifedipine therapy for 48 hours was 0.50 ± 0.18 without any signi cancy. The DV is a blood vessel that has a thin muscle.…”
Section: Nomentioning
confidence: 97%
“…Applying nifedipine does not cause redistribution of blood ow to the cerebral. 34 Changes in CPR PI blood ow before and after 48 hours after nifedipine therapy…”
Section: Nomentioning
confidence: 99%